Effective Administration Model of Professional Development of Young Teachers in Ethnic Colleges and Universities in Southwest China - Yao , Meng; Boonphadung , Suttipong (Journal of Roi Kaensarn Academi, 2024)
Promoting the development of the teaching profession has become an important issue that has been widely discussed and urgently needs to be solved in the academic field.This study investigates the effective administration model for promoting the professional development of young teachers in ethnic colleges and universities in Southwest China. Based on a review of the relevant literature, the study proposes a conceptual model that identifies three factors influencing young teachers’ professional development: individual teacher factors, school environment factors, and social environment factors. The study aims to explore the factors affect the professional development of young teachers, to provide practical guidance for enhancing the professional development of young teachers in ethnic colleges and universities in Southwest China.This study designed and developed a questionnaire on the professional development status of young teachers in ethnic universities in Southwest China and conducted the questionnaire survey and analysed using structural equation modelling .The model identifies three key categories of factors that influence young teachers’ professional development: individual teacher factors, school environment factors, and social environment factors.